The influence of Somatic Auditory Visualization Intellectualy (SAVI) Learning Method to Learning Outcome of Senior High School at Labuhanbatu District (in case on the Ecosystem Discussion) || Pengaruh Model Pembelajaran Somatic Auditory Visualization Intellectualy (SAVI) Terhadap Hasil Belajar Siswa SMA di Kabupaten Labuhanbatu (dikaji pada Materi Ekosistem) - Samini Samini (Fakultas Keguruan dan Ilmu Pendidikan Universitas Labuhanbatu, 2021)
This study aims to determine the effect of biology student learning outcomes in the subject matter characteristics of living creatures that learned by using SAVI learning method in the seventh grade students of SMPN I Panai Tengah Labuhanbatu district in learning year 2019/2020. This type of research is a quasi experimental study. The research sample consisted of two classes chosen at random cluster sampling the experimental class and control class. Total students each sample were 40 people in the control group and 40 in the experimental class. To obtain the data used in this study researchers used the test as a means of collecting data as much as 40 multiple choice questions. From the calculation of normality test the experimental class using learning Metode